Comparative Study Of Physical Education Lesson Effectiveness Between Al – Karkh 1st and 2nd Education In Baghdad Governorate - Hamad, Thamer (Journal of Physical Education, 2016)
The importance of the research lies in designing a group of axes to identify the degree of physical education lesson application effectively as well as the difference in application degrees between the 1st and 2nd Kurk educational schools. The subjects of the research were physical educators of secondary and preparatory schools for boys. The researchers used the descriptive method on (123) physical educator. The questionnaire included 5 axis each ax consist of 56 item. The reliability of the questionnaire is 80% while reliability was 0.946 according to Fakurmbak formula. The questionnaire was distributed from 24/3/2016 till 18/5/2016.  The data was collected and treated using proper statistical operations. The results showed significant statistical differences in not using physical education program effectively as well as no significant differences between controlling and experimental groups because both groups depend on the same regulations and rules. The researcher recommended taking the points of view of individuals to develop school sport as well as using standard programs in teaching physical education. Finally they recommended participating with other types of schools to develop cultural relationships and sport expertise periodically.